The relevance of CIAT`s cassava researches in the Asian and Pacific Region - Obordo, RA (International Center for Tropical Agriculture, 1978)
The most outstanding results of research on cassava at the Centro Internacional de Agricultura Tropical (CIAT) are presented and the extent to which they can be transferred or used under conditions present in Asia and the Pacific area is indicated, in particular, on physiology, var. improvement, pest and disease control, and cultural practices. The objectives of CIAT`s cassava program are given. Among the most outstanding results, the following are mentioned: compilation and dissemination of information on cassava (abstracts, photocopies, specialized monographs, reviews); accumulation of genetic material (2500 entries); identification of an optimum LAI; distribution of a total of 21,270 hybrid seeds and 50,100 open-pollinated seeds to 28 countries; obtainment of hybrid selections which outyield local cv. by 50-150 percent; and the use of HI as an indicator in the selection of cross parents, seedling selection, and single row planting trials. The contributions in disease and pest control are emphasized and recommendations related to the movement of vegetative propagating material among countries are included. (CIAT)